Wisdom as a Meditation on Life: Spinoza on Bacon and Civil History*. Issue 1 (2nd January 2016) - Van Cauter, Jo
Abstract : In letter 37 to Johannes Bouwmeester, Spinoza identifies a historiola mentis à la Bacon as an important tool for distinguishing more easily between adequate and inadequate ideas. This paper contends that Spinoza's advice is to take into account Baconian-style 'Civil History' as providing instructive material for contemplating the variety, complexity, and persistency of human passionate behaviour. Specifically, it argues that Baconian civil history forms an integral part of Spinoza's reflections on provisional morality. Although for Spinoza, philosophical beatitude ultimately demands understanding affects through their first causes – the intuitive perception of things sub specie aeternitatis – in the realm of everyday Spinoza allows for a different, more pragmatic approach to morality. This paper argues at this stage that a philosophical understanding of the mind and its affections is not needed. Spinoza, following Bacon, holds that conduct of practical affairs is particularly improved when those so engaged acquire historical knowledge of the human condition and apply it. Specifically, both authors place special emphasis on a history of men's characters, actions, and vices as providing the material basis for concrete, directly applicable moral and civil precepts.